New formalisms and literary theory - Theile, Verena; Tredennick, Linda (Houndmills, Basingstoke, Hampshire Palgrave Macmillan, 2013)
"New Formalisms and Literary Theory" examines the political motivations of a return to formalism. Together with our contributors, we want to propose and challenge the conception of New Formalism as an extension of contextual readings and as a 'mere' return to aesthetic readings. The essays gathered here encourage reflection upon New Formalism's points of intersection with other theoretical approaches and demand a reinstatement of form as the critic's central focus, form, that is, as it reflects a culture's creative imagination and historicizes itself within and against a politically charged background.
Part I: Introduction -- 1. New Formalism(s): a prologue / Verena Theile -- PART II: Theory -- 2. Toward a New Formalism: the intrinsic and related problems in criticism and theory / Fredric V. Bogel -- 3. Doing genre / Group Phi -- Part III: Practice -- 4. Inventing an ancestor: the scholar-poet and the sonnet / Edward Brunner -- 5. From close reading to cross-reading: Sacco-Vanzetti poetry and the politics of New Formalism / Bartholomew Brinkman -- 6. Re-reading for forms in Sir Philip Sidney's Defence of Poesy / Corey McEleney and Jacqueline Wernimont -- 7. Collecting body parts in Leonardo's cave: Vasari's Lives and the erotics of obscene connoisseurship / Harry Berger Jr -- 8. Form as a pattern of thinking: Cognitive poetics and New Formalism / Karin Kukkonen -- Part IV: Pedagogy -- 9. Reading like a writer: a creative writer's approach to New Formalism / Kelcey Parker -- 10. Punk bodies, Jorie Graham, and the draft Itself: notes toward a lyric Formalism / Cynthia Nichols -- 10. 'One another's hermitage': New Formalist pedagogy / Linda Tredennick.
Includes bibliographical references (pages 242-255) and index.
Keywords: Formalism (Literary analysis)